Combining ability and heterosis for grain iron biofortification in bread wheat. (31st December 2019) - Younas, Abia; Sadaqat, Hafeez Ahmad; Kashif, Muhammad; Ahmed, Nisar; Farooq, Muhammad
Abstract: BACKGROUND: Iron is one of the nutrients that is essential for the human body. Despite the abundance of iron on earth, about two billion people worldwide are affected by iron deficiency. Iron biofortification of wheat, instead of supplementation and food fortification, provides a pragmatic approach to solve the problem of iron deficiency. In this study, 144 diverse wheat genotypes were evaluated for grain iron and yield potential, to estimate the potential for the iron biofortification of high‐yielding wheat varieties. RESULTS: Genotypes did not differ significantly across the species, but within species the differences were significant for grain iron content and the phytate:iron molar ratio. Triticum aestivum (bread wheat) had the highest yield potential with more diversity than other Triticum species. Genotypes with high iron contents were crossed with high‐yielding genotypes in line × tester fashion to check the gene action controlling these traits. The combining ability analysis showed non‐additive gene action controlling grain iron, grain phytate, and grain yield. Heterosis manifestation also indicated some transgressive segregates with high specific combining ability effects. CONCLUSION: There was considerable genetic potential for improving the grain iron content in the germplasm to provide an economical and long‐lasting solution to benefit an iron‐deficient population. Triticum aestivum had the highest variation and potential for iron biofortification. This study indicated the possibility of simultaneous improvement in grain iron and grain yield by producing a new variety through continuous selective breeding. © 2019 Society of Chemical Industry